2019
DOI: 10.1016/j.bpj.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Transmembrane Helix Mutations on Cytochrome P450-Membrane Interactions and Function

Abstract: Human cytochrome P450 (CYP) enzymes play an important role in the metabolism of drugs, steroids, fatty acids, and xenobiotics. Microsomal CYPs are anchored in the endoplasmic reticulum membrane by an N-terminal transmembrane (TM) helix that is connected to the globular catalytic domain by a flexible linker sequence. However, the structural and functional importance of the TM-helix is unclear because it has been shown that CYPs can still associate with the membrane and have enzymatic activity in reconstituted s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 58 publications
5
23
1
Order By: Relevance
“…CYP 2C9 mainly adopted a class A orientation, which has lower α, β and heme-tilt angles, and CYP 2C19 adopted a class B orientation. The class B orientation is similar to the orientations observed in simulations with the same bilayer and force field for CYP 3A4 and N-terminal mutants of CYP 17A1 and CYP 19A1, with measured heme-tilt angles of about 60° [27]. CYP 2C9 thus appears to be unusual in this set of CYPs (simulated under the same conditions) in adopting an orientation with a lower heme-tilt angle.…”
Section: Concluding Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…CYP 2C9 mainly adopted a class A orientation, which has lower α, β and heme-tilt angles, and CYP 2C19 adopted a class B orientation. The class B orientation is similar to the orientations observed in simulations with the same bilayer and force field for CYP 3A4 and N-terminal mutants of CYP 17A1 and CYP 19A1, with measured heme-tilt angles of about 60° [27]. CYP 2C9 thus appears to be unusual in this set of CYPs (simulated under the same conditions) in adopting an orientation with a lower heme-tilt angle.…”
Section: Concluding Discussionsupporting
confidence: 72%
“…These differences can be attributed in large part to differences in both the protein and the lipid force field used. Our studies have shown that the force field used in the current work produces results in better agreement with experimental data for simulations of CYP-membrane systems, including excellent agreement with linear dichroism measurements of the heme-tilt angle of CYPs in Nanodiscs [25,26,27].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Numerous experimental data are available on the structure of the NOS heme domain in the closed state, but several aspects remain to be elucidated. For comparison with a homolog, extensive in silico studies (e.g., microsecond all-atom and coarse-grain MD, docking) have been reported on P450 enzymes [ [73] , [74] , [75] , [76] , [77] , [78] ], including the investigation of the structure of the active site, substrate tunneling and binding modes, mutational effects, and interaction with membranes. These show the usefulness of molecular modeling in a context similar to NOSox.…”
Section: Nos Structurementioning
confidence: 99%
“…The globular domain of tomato C22DES interacts with the ER in the absence of TMH It has been reported that the globular domain of several CYP proteins interacts with the ER membrane in the absence of the transmembrane domain (32)(33)(34)(35). To determine if this is the case in tomato C22DES, a N-terminal truncated form of the enzyme lacking the TMH region (residues 2 to 27) was fused to the Nterminal end of RFP and the resulting protein (C22DESΔ2-27-RFP) transiently expressed along with TMH-GFP in N. benthamiana leaves.…”
Section: Tmh Is Su Cient To Target and Retain Tomato C22des In The Ermentioning
confidence: 99%